TIGA SERANGKAI PEMICU KEINGINAN INSTAN : STUDI TENTANG DAMPAK INFLUENCER MARKETING, VIRAL MARKETING DAN ONLINE CUSTOMER REVIEW TERHADAP IMPULSIVE BUYING GEN Z DI KOTA MAKASSAR - Tommy Thios; Austin Setyawan Oendy; Sharleen Angelica Wijaya Valerie Aurora; Winy Aurellia Widhyadari Wijaya; Erwin Erwin (LPPM STIE Muhammadiah Bandung, 2025)
This study aims to analyze the influence of Influencer Marketing, Viral Marketing, dan Online Customer Review (OCR) on Impulsive Buying behavior among Generation Z in Makassar City. This research method uses a quantitative approach, with data collected through a 5-Point Likert scale questionnaire distributed to 156 Generation Z respondents (aged 13-28 years) in Makassar City. The data were analyzed using PLS-SEM (a statistical modeling method) with WarpPLS 8.0 software. The results show that Viral Marketing has a significant positive effect on Impulsive Buying, meanwhile Influencer Marketing and Online Customer Review do not show significant effects. These findings suggest that marketing strategies focused on viral content are more effective in triggering Impulsive Buying among Generation Z in Makassar City, compared to using influencers or customer reviews. This study provides practical contributions for fashion businesses to optimize their marketing strategies. Academically, it enriches literature on the impact of Influencer Marketing, Viral Marketing, and Online Customer Review (OCR) in Digital Marketing, particularly Generation Z.